2018
DOI: 10.1002/gj.3236
|View full text |Cite
|
Sign up to set email alerts
|

Carboniferous tectonic configuration of the Yining Massif in Western Tianshan, NW China

Abstract: The tectonic evolution and configuration of the Carboniferous trench‐arc‐basin system (TABS) in the Yining Massif (Western Tianshan, NW China) have long been controversial. The question of the existence of an ancient ocean basin and its subduction polarity is crucial to address this issue. In this study, we suggest that the Early Carboniferous calc‐alkaline volcano‐sedimentary rocks were formed in a fore‐arc/back‐arc basin system, whereas the Late Carboniferous bimodal volcanic rocks and their associated sedim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 39 publications
(63 reference statements)
0
4
0
Order By: Relevance
“…In contrast, the Late Carboniferous volcanic rocks show distinct differences in rock assemblages, geochemistry and tectonic settings. They are dominated by alkaline rocks and tholeiitic basalts (Li et al, 2018b). A remarkable feature of the Late Carboniferous volcanism is the occurrence of typical bimodal volcanic suites at the Wusun Mountain, Yining Block, with zircon U-Pb ages of ca.…”
Section: Geological Settingmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, the Late Carboniferous volcanic rocks show distinct differences in rock assemblages, geochemistry and tectonic settings. They are dominated by alkaline rocks and tholeiitic basalts (Li et al, 2018b). A remarkable feature of the Late Carboniferous volcanism is the occurrence of typical bimodal volcanic suites at the Wusun Mountain, Yining Block, with zircon U-Pb ages of ca.…”
Section: Geological Settingmentioning
confidence: 99%
“…The C 1 a shows neritic, marine-continental transitional affinities, and massive carbonates, sandstones and siltstones, as well as a well-developed rich assemblage of shallow-water fossils (Bai et al, 2015). Relative to the C 1 d, the C 2 y is dominated by a typical bimodal volcanic suite related to continental lift (Li et al, 2018b;Ning et al, 2019). In addition, Permian to Jurassic strata overlie the Carboniferous outcrop and Late Devonian to Permian granitoids are also exposed in this area, which occur as small plutons or dikes intruding the Late Paleozoic volcanic-sedimentary sequences (Bao et al, 2018).…”
Section: Geology Of the Wusun Mountain And Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…The mafic end‐member rocks indicate a mantle source, whereas silicic end‐member rocks are A‐type granites, formed by partial melting of the thinned lithosphere crust triggered by mafic magma upwelling. Y. Li et al ( ) studied the tectonic configuration of Carboniferous rocks in the Yining Massif of West Tianshan. They concluded that the Early Carboniferous volcano‐sedimentary rocks formed in a fore‐arc/back‐arc setting, similar to that of present‐day Japanese island arc, whereas the Late Carboniferous bimodal volcanic rocks and sediments formed in a continental rift setting after the Junggar‐Tarim collision.…”
Section: Volume 3: Structure and Main Themesmentioning
confidence: 99%